CD10 positive thyroid marginal zone non-Hodgkin lymphoma. - Millar, E K (1999)
A 72 year old woman presented with swelling of the right lobe of her thyroid gland. Fine needle aspiration and flow cytometry showed a clonal population of B cells expressing CD10 and a diagnosis of follicle centre cell lymphoma was made. Subsequent excision of the thyroid showed the typical histological features of a marginal zone non-Hodgkin lymphoma. Polymerase chain reaction showed no evidence of t (14;18). Immunohistochemistry confirmed CD10 positivity and LN1 (CDw75) expression. This is only the second report of aberrant expression of CD 10 by a marginal zone lymphoma.